Blastocystis sp. : Evaluation of polyclonal antibody prepared from crude protein for serological diagnosis using Rabbit serum - Septian Hakim Susantoputro; Lucia Tri Suwanti; Rahadju Ernawati; Mufasirin Mufasirin; Setiawan Koesdarto; Wiwiek Tyasningsih; Heni Puspitasari (Syiah Kuala University, 2020)
The diagnosis of Blastocystis infection is still based on the clinical sign which is not specific and there is no available serologic test for it. This study aimed to evaluate the polyclonal antibody prepared form crude protein of Blastocystis for the development of the Blastocystis serological test. Crude protein was extracted from the yeast of Blastocystis sp, then inoculated into rabbits to produce the antibody of crude protein. The serum of rabbits would be collected before and after immunization to compare the antibody titer. The profile of crude protein was analyzed using SDS-Page. The rabbit serum was analyzed using ELISA and Western Blot. The SDS-Page result showed bands in 100 kDa, 90 kDa, 70 kDa, 60 kDa, 58 kDa, 50 kDa, 40 kDa, 35 kDa, 30 kDa and 27 kDa. The ELISA assay showed that there was an increase in antibody titer of crude protein after immunization. Western Blot showed that three proteins (30 kDa, 40 kDa and 50 kDa) having immunogenicity characteristic. It is concluded that protein 30 kDa, 40 kDa and 50 kDa prepared from the crude protein of Blastocystis sp. can be used for developing a serologic test for Blastocystis infection. Keywords: Blastocystis sp, Crude Protein, Polyclonal Antibody .